Scientists’ Perspectives on the Demarcation Problem - Mustafa Efe Ateş; Mehmet İnce; Cenk Barın Bora (Felsefe Arkivi)
The demarcation problem, concerning the establishment of a specific criterion for distinguishing science from non-science or pseudoscience, stands as one of the central issues in the philosophy of science. Considering the extant body of literature, philosophers, particularly those specializing in the philosophy of science, gain insight into the nature of science through logical language analysis and/or historical examination. In doing so, they aim to demarcate science from other pursuits. Nevertheless, this paper takes a distinct approach, diverging from the conventional viewpoint of philosophers and instead adopting the perspective of scientists. To achieve this, we conducted a series of qualitative interviews involving 30 scientists, each of whom holds a professorship in their respective fields. By conducting these interviews, we aimed to reveal the scientists’ perspectives on the demarcation problem and then evaluate their viewpoints. Following the evaluation of these perspectives, three key findings became evident. First, a significant majority of the responses obtained regarding the demarcation problem align well with prevailing philosophical views found in the existing literature. The responses that closely match the dominant philosophical approaches have been highlighted in the article’s thematic sections. Second, a lack of consensus also exists among scientists regarding the demarcation problem, similar to the lack of consensus among philosophers. However, despite this absence of agreement, a balance appears to exist between different conflicting viewpoints among scientists. Third and finally, scientists generally lack strong familiarity with the fundamental philosophical issues related to the demarcation problem. Although this finding relies on non-quantitative measures, detailed analysis supports this conclusion. Based on these findings, we conclude that adopting different approaches to conducting interviews could lead to more nuanced outcomes.